2014
DOI: 10.3109/10717544.2014.898715
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and characterization of albumin microspheres containing norcantharidate for liver tumor targeting

Abstract: The objectives of this study were first to encapsulate norcantharidate into albumin microspheres by the emulsion crosslinking method and second to characterize the microspheres in terms of the morphological examination, particle size, and encapsulation efficiency. The in vitro release of norcantharidate from the microspheres was studied by using the dialysis bag method. Pharmacokinetics and biodistribution studies were used to evaluate the advantages of microspheres than the conventional formulations. The micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Moreover, norcantharidin is effective against primary liver cancer . However, a drawback that limits the clinical use of cantharidin derivatives is their short half‐life, which would require frequent administrations to patients . To overcome this limitation, cantharidin derivatives have been incorporated into various microspheres that allow to prolong their half‐life and to minimize any risk of systemic toxicity …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, norcantharidin is effective against primary liver cancer . However, a drawback that limits the clinical use of cantharidin derivatives is their short half‐life, which would require frequent administrations to patients . To overcome this limitation, cantharidin derivatives have been incorporated into various microspheres that allow to prolong their half‐life and to minimize any risk of systemic toxicity …”
Section: Introductionmentioning
confidence: 99%
“…Recently, norcantharidin has been encapsulated into human serum albumin (HSA) microspheres since this plasma protein is a very appealing biocompatible carrier for drug delivery . Pharmacokinetic studies in rats showed that compared to the intravenous injection of free norcantharidin, the half‐life of the drug encapsulated into HSA microspheres increases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guar gum microspheres were prepared by the emulsion cross-linking technique [15,16]. Briefly, BUD (25 mg) and guar gum (125 mg) were added to 5 mL of methylene chloride.…”
Section: Methodsmentioning
confidence: 99%